2016
DOI: 10.1038/srep35626
|View full text |Cite
|
Sign up to set email alerts
|

Artificial light at night affects body mass but not oxidative status in free-living nestling songbirds: an experimental study

Abstract: Artificial light at night (ALAN), termed light pollution, is an increasingly important anthropogenic environmental pressure on wildlife. Exposure to unnatural lighting environments may have profound effects on animal physiology, particularly during early life. Here, we experimentally investigated for the first time the impact of ALAN on body mass and oxidative status during development, using nestlings of a free-living songbird, the great tit (Parus major), an important model species. Body mass and blood oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 83 publications
2
62
3
Order By: Relevance
“…Melatonin is a thyroid antagonist thought to have a role in metamorphosis, as reported in amphibian studies (Wright, ). However, our findings are in contrast to comparable studies, exploring the effect of dim night lighting on offspring growth that found reduced juvenile to adult development times and reduced body size for ALAN individuals (Raap et al., ; van Geffen et al., ). One potential explanation for the observed variation in development is that the 0 lx condition with its 12 hr dark period may have triggered a short day‐length response in T. commodus , a species with demonstrated facultative diapause (Hogan, , ).…”
Section: Discussioncontrasting
confidence: 99%
“…Melatonin is a thyroid antagonist thought to have a role in metamorphosis, as reported in amphibian studies (Wright, ). However, our findings are in contrast to comparable studies, exploring the effect of dim night lighting on offspring growth that found reduced juvenile to adult development times and reduced body size for ALAN individuals (Raap et al., ; van Geffen et al., ). One potential explanation for the observed variation in development is that the 0 lx condition with its 12 hr dark period may have triggered a short day‐length response in T. commodus , a species with demonstrated facultative diapause (Hogan, , ).…”
Section: Discussioncontrasting
confidence: 99%
“…We found that the responses of nighttime activity and cort levels were dependent on the color temperature of the LED, whereby exposure to 5000 K LED night‐lights, but not 3000K or control treatments, increased nighttime activity and cort levels over a three week experimental period. Additionally, we used a low level of illuminance (0.3 lx) not much brighter than what animals may experience under a full moon (Rich & Longcore, ), as compared to previous studies (Bedrosian, Aubrecht, Kaugars, Weil, & Nelson, ; Burger, ; Raap et al., , b; Titulaer, Spoelstra, Lange, & Visser, ; Yorzinski et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…These effects are evident even at relatively low levels of ALAN (≤30 lx), typical of the light environment in some urban and peri‐urban spaces. Field studies demonstrate a negative relationship between the presence of dim ALAN (≤5 lx) and reproductive success and juvenile growth in birds (Dominoni, Goymann, Helm, & Partecke, ; Dominoni, Quetting, & Partecke, ; Raap et al., ) and reproduction in mammals (LeTallec, Thery, & Perret, ; Robert, Lesku, Partecke, & Chambers, ), whereas laboratory experiments in hamsters and rats link exposure to dim ALAN (between 1 and 5 lx) with increases in tumor growth rates (Blask, Dauchy, Brainard, & Hanifin, ) and immune suppression (Bedrosian, Aubrecht, Kaugars, Weil, & Nelson, ). Similar responses to chronic exposure to dim ALAN (between 10 and 30 lx) are observed in invertebrates.…”
Section: Introductionmentioning
confidence: 99%